Sistem Informasi Manajemen Kepegawaian Penentuan Karyawan Terbaik Menggunakan Metode Analytical Hierarchy Process (AHP) Berbasis Web - Sindhu Rakasiwi; Haryo Kusumo; Rifal Winazar (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
In the era of information and technological developments that are very rapid as it is today, in the context of managing human resources in a company or what is known as a personnel management information system. The problems faced by PT. Nerangi Sarana Karya, namely until now, the staffing data management is still using a manual system that is not well computerized, does not have a database as a data storage medium, data sharing is not via the network and still uses hardcopy printouts. Seeing the problems that occur in the personnel administration subdivision of PT. Nerangi Sarana Karya, the author intends to develop a web-based personnel information system (SIMPEG) to hide staffing master data, employee data, promotions, and periodic salary increase data. using PHP and MySQL. The system development method that I use is AHP. In the end, this system can provide output to its users in the form of a promotion decree, a regular salary increase decree and employee reports.